The reporting quality of N‐of‐1 trials and protocols still needs improvement. Issue 4 (2nd August 2022) - Wei, Zhipeng; Chu, Xiajing; Han, Jiani; Zhang, Na; Li, Yanfei; Yang, Chaoqun; Wang, Qi; Li, Jiang; Belal, Ahmed Atef; Yan, Peijing; Li, Xiuxia; Yang, Kehu
Abstract: Objective: To evaluate the reporting quality of single‐patient (N‐of‐1) trials and protocols based on the CONSORT Extension for N‐of‐1 trials (CENT) statement and the standard protocol items: recommendations for interventional trials (SPIRIT) extension and elaboration for N‐of‐1 trials (SPENT) checklist to examine the factors that influenced reporting quality. Methods: Four electronic databases were searched to identify N‐of‐1 trials and protocols from 2015 to 2020. Quality was assessed by two reviewers. We calculated the overall scores based on binary responses in which "Yes" was scored as 1 (if the item was fully reported), and "No" was scored as 0 (if the item was not clearly reported or not definitely stated). Results: A total of 78 publications (55 N‐of‐1 trials and 23 protocols) were identified. The mean reporting score (SD) of the N‐of‐1 trials and protocols were 29.24 (0.89) and 29.61 (1.83), respectively. For the items related to outcomes, sample size, allocation concealment protocol, and informed consent materials, the reporting quality was low. Our results showed that the year of publication ( t = ‐0.793, p = 0.872 for the trials and t = 1.352, p = 0.623 for the protocols) and the impact factor of the journal ( t = 1.416, p = 0.619 for the trials and t = 0.359, p = 0.667 for the protocols) were not factors associated with better reporting quality. Conclusion: With the publication of the CENT 2015 statement and the SPENT 2019 checklist, authors should adhere to the relevant reporting guidelines and improve the reporting quality of N‐of‐1 trials and protocols.